Optimizing Islamic Religious Education: A Case Study on Curriculum Management in Planning, Implementation, and Evaluation - Samsuddin Samsuddin; Irma Suryani Siregar (STAI Hubbulwathan Duri, 2024)
This study examines the management of Islamic Religious Education (PAI) at SDIT Al-Munawwar, Panyabungan, Mandailing Natal. The focus is on the planning, implementation, and evaluation processes within the learning management framework, highlighting challenges and strategies for improvement. The research employs a qualitative approach using a case study method. Data were collected through interviews, observations, and document analysis to gain insights into the PAI learning management practices and their outcomes. The findings indicate that the management of PAI at SDIT Al-Munawwar is effectively conducted. Planning involves structured lesson plans integrating Islamic values into the curriculum. Implementation is characterized by the use of innovative pedagogical methods, including project-based and problem-based learning, enhanced by digital technologies. These approaches have significantly improved student engagement and comprehension. Comprehensive evaluation strategies, including both formative and summative assessments, effectively address cognitive, affective, and psychomotor domains. Despite its strengths, the school faces challenges in adapting to educational technologies and enhancing teacher competencies. To overcome these issues, SDIT Al-Munawwar has initiated ongoing teacher training programs and fostered collaboration between the school, families, and the broader community. The study underscores the importance of integrated and innovative learning management in PAI education. While significant progress has been made, continued efforts in professional development and technological adaptation are essential for sustained success.